plaTform fOr Urinary tract infection diagnostiC evAluatioN (TOUCAN): a protocol for a prospective diagnostic accuracy study of point-of-care testing in patients suspected of acute uncomplicated urinary tract infection in primary care clinics in England - Thomas R Fanshawe; Philip J Turner; Gail N Hayward; Margaret Glogowska; Alastair D Hay; Michael Moore; Mark Lown; Christopher C Butler; Mandy Wootton; Mark H Wilcox; Jane Freeman; Nicola Kenealy; et al. (BMJ Open)
Introduction Acute uncomplicated urinary tract infection (UTI) is a common condition with potentially serious sequelae that is mostly diagnosed and managed in primary care settings. Around half of all women have a UTI in their lifetime, and a quarter experience an infection caused by organisms resistant to more than one antibiotic. Reducing inappropriate prescribing of antibiotics is a core tenet of antimicrobial stewardship. However, current diagnostics for UTI are unfit for purpose in acute (highest prescribing) settings, being too slow to inform the required immediate decision-making and often confounded by sample contamination.Rapid point-of-care diagnostic tests (POCTs) that facilitate timely decision-making are potential solutions to this problem. Several such tests have reached advanced stages of technology readiness, but their diagnostic performance has not been evaluated in primary care with clinical users. To progress novel tests towards implementation, a diagnostic field study is required, to allow for parallel and sequential evaluation of multiple tests in a primary care population.Methods and analysis We will recruit participants assigned female at birth from primary care clinics in England who contact their clinic with symptoms of acute uncomplicated UTI. Eligible participants will complete a short questionnaire to capture symptoms and symptom severity and will provide a urine sample. Samples will be split and initially tested using novel index tests (POCTs) and conventional urinalysis ‘dipstick’ at the primary care clinic. The second part of the sample will be processed at a National Health Service-based reference laboratory using a modified reference standard including microscopy, microbiological culture, pathogen speciation and antimicrobial susceptibility testing. The UTI reference standard culture, although based on the national methods, is modified to provide accurate bacterial counts, better to define a microbiological diagnosis of UTI. Susceptibility testing will be performed using ‘gold-standard’ methods, not usually performed in diagnostic laboratories. The primary outcome will be the diagnostic performance (sensitivity, specificity, positive and negative predictive values) of POCTs for detection of UTI and antimicrobial susceptibility for POCTs that include antimicrobial susceptibility testing. Secondary outcomes will include the symptom profile of patients presenting with uncomplicated UTI, a theoretical determination of how use of POCT results might change prescribing, an understanding of POCT failure rate and qualitative capture of the experiences of those using the POCT to deliver the study in primary care clinics.Ethics and dissemination Ethical approval was received from the London Central Research Ethics Committee (23/LO/0371) and the UK Health Research Authority. We will publish the findings of The plaTform fOr Urinary tract infection diagnostiC evAluatioN evaluations in peer-reviewed medical journals and more broadly following a dissemination plan formulated by a communications specialist in consultation with patients and the public.Trial registration number ISRCTN80937472.